1986
DOI: 10.1021/j100273a021
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond flash photolysis of chromium(III) coordination complexes

Abstract: 87assume the dimers have no internal energy [Eint(2) = 01, then the internal energy of the remaining monomers can be. calculated from eq 8 as 0.85 X J/molecule (427 cm-I). On the other hand, the maximum value for Ein,(2) is Do = 196 cm-I; otherwise, the dimers would dissociate. With this value, Eint(l) = 0.68 X J/molecule (340 cm-I). In both these calculations, E,(l) has been taken to be equal to AHvap10 These values for the internal energy are within experimental error of that previously reported, (0.97 f 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…These observations suggest that the higher energy irradiation populates quartet Franck-Condon states at energies above the quartet/doublet crossing point such that quartet to doublet ISC effectively competes with vibrational cooling. This interpretation was supported by ps laser studies on several Cr(III) complexes that demonstrated a rise time for 2 E g formation shorter than the time response of the instrument (1-2 ps) [59,60]. More recent studies on Cr(acac) 3 indicate that k ISC > 1 × 10 13 s −1 , thus ISC from such Franck-Condon states is at least competitive with VR to the lowest quartet [54].…”
Section: Photophysicsmentioning
confidence: 89%
“…These observations suggest that the higher energy irradiation populates quartet Franck-Condon states at energies above the quartet/doublet crossing point such that quartet to doublet ISC effectively competes with vibrational cooling. This interpretation was supported by ps laser studies on several Cr(III) complexes that demonstrated a rise time for 2 E g formation shorter than the time response of the instrument (1-2 ps) [59,60]. More recent studies on Cr(acac) 3 indicate that k ISC > 1 × 10 13 s −1 , thus ISC from such Franck-Condon states is at least competitive with VR to the lowest quartet [54].…”
Section: Photophysicsmentioning
confidence: 89%
“…Fluorescence or delayed fluorescence has been searched for in room-temperature solution studies by many workers, and only one report remains viable. Consequently, little is known about the energy of the thermalized quartet excited state in solution and the reported rise time for doublet phosphorescence, <1 ps, implies that this state may have only a fleeting existence . Regarding its chemical reactivity, however, doublet quenching experiments have clearly shown that photochemistry occurs from the quartet state as there is often an unquenchable component of reaction.…”
Section: Background Spectroscopy and Photophysicsmentioning
confidence: 99%
“…In the present work ) and in our earlier communication (Serpone 1984) we employed a solid-state Nd:Yag laser svstem (^30 ps pulses; 2-3 mj/pulse) ; photon flux per pulse ^ 10 16 -10 lS 7 photons/cm 2 , some 5-6 orders of magnitude greater than that used by Rojas (1986Rojas ( 1987 3,4,7, phen) revealed that excitation (355 nm) of all these complexes results in a fast emission component below 650 nm that decays in ^ 50 ps (Fig. 2a), and, with the exception of NN = 5-Phphen, 4,4'-Ph^bpy, and Cr(terpy) 2 3 + , a slow emission rise at ^ 700 nm.…”
Section: Resultsmentioning
confidence: 94%
“…1980,35b,554 (9) Strand, D. unpublished results (10) Schonherr, T., Linder, R.; Eyring, G. Z. Naturforsch.1983,38a,736 (11) are a few ps or less (Kirk 1976;Rojas 1986Rojas 1987Pyke 1978 ;LeSage 1983 ;Nicollin 1980). Recently, we reported (Serpone 1984) that 355-nm excitation of Cr(bpy) 3 and Cr(4,7-Me 2 phen) 3 3+ in 1M HCl aqueous media results in a grow-in of the luminescence from their 2 Tj_/ 2 E states with x(rise) ^ 10-20 ns, attributed to intersystem crossing from the quartet to the doublet manifolds.…”
Section: Unk-bibliofhekmentioning
confidence: 98%